Research and Analysis of Global Weather Extremes Affecting Civil Engineering Construction Schedules Based on LSTM Algorithm (Journal of Environmental Science Studies, 2022)
The occurrence of extreme weather events will cause serious harm to natural ecosystems, human social economy and construction sites. Large-scale construction projects have a long cycle and complex construction environment, and the schedule control is obviously disturbed by meteorological and other factors. Risk control of schedule delays is an important part of project risk management. The study of extreme weather events has become a key focus and hotspot in meteorological and climate science research in the context of global change. This paper proposes a more objective approach to defining extreme climate events from the study of extreme climate event uncertainty. On this basis, the spatial and temporal characteristics of extreme temperature and precipitation in recent decades are analysed. Considering the variability of precipitation and temperature, an idea is proposed to study extreme continuous precipitation events, and the mechanism of extreme precipitation occurrence in the region is explored. Finally, the LSTM model data are used to carry out studies and projections of changes in extreme climate events under different future scenarios.